A Qualitative Investigation of WhatsApp Interaction for English Language Grammar Learning - Nagaletchimee Annamalai; Najah Rajeh Alsalhi; Mohd Elmagzoub Eltahir; Bilal Mohammed Zakarneh; Kamariah Yunus; Samer H. Zyoud (SAGE Open)
This qualitative case study aimed to examine pre-service teachers’ and teacher educators’ interactions during their English grammar lessons via the WhatsApp platform. The Community of Inquiry (CoI) model was employed to categorize the WhatsApp interactions based on social, cognitive and teacher presences. Participants wrote their reflections for an in-depth understanding of the phenomenon that is being investigated. The cognitive, social and teaching presences were evident during their interactions on the WhatsApp platform. Among them, cognitive presence was identified to be the most common interaction. Participants used the WhatsApp platform to explore and integrate ideas related to English grammar. The platform also allowed them to construct sentences based on the rules and knowledge gained during their interactions. The teacher acted as a facilitator assisting learners rather than passively teaching learners the “correct” way to learn the English language by creating opportunities for learners to notice grammatical rules. For social presence (SP), the use of emoticons was dominant. The reflective writing demonstrated positive learning experiences. The study concluded that WhatsApp has the potential to be a worthwhile platform for English grammar learning if instructors are able to optimize the features offered in an application for effective interactions and collaborative dialogues.